Characterization of a rat model of moderate chronic renal failure: focus on hematological, biochemical, and cardio-renal profiles - Garrido, P. (2009)
The pathophysiological modifications underlying chronic which will determine the moment to start therapy. As there is yet limited information about animal models of moderate chronic renal failure, we intended to perform a complete characterization 60 of the hematological and cardio-renal alterations induced by partial nephrectomy. Blood samples from control and chronic renal failure rats were collected at 0, 3, 9, and 15 weeks in order to evaluate renal function, hematological parameters, iron metabolism, blood lipids, peripheral sympathetic nervous system, and 65 inflammatory and redoz status markers. BP, tissues trophy indexes, and kidney histomorphology were also assessed. Our data are consistent with a sustained moderate degree of chronic renal failure with a quickly compensated modest anaemia, though presenting iron metabolism disturbances. Despite the reasonable degree of functionality of the remnant kidney, as sug- 70 gested by the anaemia correction and by the kidney hypertrophy and moderate lesions, several important cardiovascular modifications were developed. Our model presented hypertension, dyslipidemia, erythropoietic disturbances, sympathetic activation, and oxidative stress. This model might be a good tool to study the cellular/molecular mechanisms underlying moderate stages of chronic renal failure and to evaluate the therapeutic efficacy for prevention and treatment/correction of cardio-renal anaemia syndromes and complications in early stages.